Kurikulum Berbasis Budaya untuk Sekolah Dasar: Menyelaraskan Pendidikan dengan Identitas Lokal - Zahrika, Nazala Aprian; Andaryani, Eka Titi (Medan Resource Center, 2023)
In an era of globalization that is increasingly curbing local cultural diversity, this article raises the issue of the importance of developing a culture-based curriculum for elementary school level. This approach aims to align education with local identity, revive students' sense of pride and understanding of their cultural heritage, and promote cultural diversity in the teaching and learning process. In the midst of the challenges of globalization which has the impact of cultural homogenization, a culture-based curriculum is the only strong bulwark to defend and maintain the cultural roots of a nation. This article reviews the background, principles, benefits, and steps for implementing a culture-based curriculum for elementary schools, while also discussing challenges that may arise and solutions that can be implemented. In conclusion, education that reflects local identity through a culture-based curriculum is a leading step in preserving cultural heritage, supporting student development, and creating a more inclusive society.